The Effect of Work Environment and Job Rotation on Employee Performance with Job Satisfaction as a Mediation Variable - Amiriyyah, Rofilah; Rumijati, Aniek; Mursidi, Mursidi (University of Muhammadiyah Malang, 2025)
Human resources are crucial to the success of an organization. One of the efforts to develop human resources is through job rotation. Enhancing the quality of employee performance includes improving the work environment. This study aims to analyze the influence of the work environment and job rotation on employee performance through job satisfaction. The research was conducted at the Representative Office of BKKBN in Central Kalimantan Province using a questionnaire with a sample of 40 civil servants, employing PLS-SEM analysis techniques. The research findings indicate a significant influence of the work environment on job satisfaction. However, the work environment does not significantly affect employee performance. On the other hand, job rotation shows a non-significant influence on both job satisfaction and employee performance. The results of the indirect effect analysis suggest that job satisfaction does not mediate the effects of the work environment and job rotation on employee performance.